Zr: XFe3- xO4 (0.01 ≤ x ≤ 1.0) nanoparticles: A possible magnetic in vivo switch - Prasad N.K.; Srivastava M.; Alla S.K.; Danda J.R.; Aditya D.; Mandal R.K. (My University, 2025)
Magnetic hyperthermia holds promise for alternative therapeutic use for cancer ailments having the least side effects. It has issues pertaining to the temperature increase observed during treatment. This study primarily discusses the magnetic hyperthermia response of ZrxFe3-xO4 (0.01 ≤ x ≤ 1.0) based ferrofluids nanoparticles at different concentrations. Structural characterization through X-ray diffraction (XRD) and selected area electron diffraction (SAD) patterns suggests the formation of a single phase in the whole range of Zr-substituted Fe3O4 studied. Even energy dispersive X-ray (EDX) spectrometry analyses confirm the doping of Zr4+ ions into Fe3O4. The observed variation in the saturation magnetization (MS) was found to be a function of Fe2+, Fe3+ and Zr4+ ion concentration at the interstitial voids of Fe3O4. The ferrofluids displayed stability near the therapeutic temperature range of 42-46 °C for various combinations of the amplitude and frequency of the alternating magnetic field. The temperature stability is unexpected in view of high Curie temperature (TC > 300 °C). This behaviour of the ferrofluid was observed for concentrations of the magnetic nanoparticles up to 40 mg mL-1. Such an observation is lacking in the literature available. © 2016 The Royal Society of Chemistry.